Structure and conformational analysis of spiroketals from 6-O-methyl-9(E)-hydroxyiminoerythronolide A - Čikoš, Ana; Ćaleta, Irena; Žiher, Dinko; Vine, Mark B.; Elenkov, Ivaylo J.; Dukši, Marko; Gembarovski, Dubravka; Ilijaš, Marina; Dragojević, Snježana; Malnar, Ivica; Alihodžić, Sulejman (Beilstein Journal of Organic Chemistry, 2015)
Three novel spiroketals were prepared by a one-pot transformation of 6-O-methyl-9(E)-hydroxyiminoerythronolide A. We present the formation of a [4.5]spiroketal moiety within the macrolide lactone ring, but also the unexpected formation of a 10-C=11-C double bond and spontaneous change of stereochemistry at position 8-C. As a result, a thermodynamically stable structure was obtained. The structures of two new diastereomeric, unsaturated spiroketals, their configurations and conformations, were determined by means of NMR spectroscopy and molecular modelling. The reaction kinetics and mechanistic aspects of this transformation are discussed. These rearrangements provide a facile synthesis of novel macrolide scaffolds.
Keywords: configuration; conformation; 6-O-methyl-9(E)-hydroxyiminoerythronolide A; reaction mechanism; spiroketal